Catalogue of type specimens of invertebrates in the collection of the Instituto Nacional de Pesquisas da Amazônia, Manaus, Brazil. V. Arachnida: Araneae, Opiliones and Scorpiones - Saturnino, Regiane; Tourinho, Ana Lúcia; de Azevedo, Clarissa Salette; Baptista, Renner L. C.; Magalhães, Célio (Zootaxa, 2009)
A catalogue of type specimens of Araneae, Opiliones and Scorpiones deposited in the Invertebrate Collection of the Instituto Nacional de Pesquisas da Amazônia (INPA), Manaus, Brazil, is presented. There are 52 holotypes and 99 lots of paratypes for 68 species of Araneae; 6 holotypes and 18 lots of paratypes for 7 species of Opiliones; and 19 holotypes and 20 lots of paratypes for 19 species of Scorpiones.